Use of CT Angiography and Digital Subtraction Angiography in Patients with Ruptured Cerebral Aneurysm: Evaluation of a Large Multihospital Data Base - McDonald, J.S. (AJNR Am J Neuroradiol, 2013)
BACKGROUND AND PURPOSE: Both CT angiography and digital subtraction angiography are used to detect aneurysms in patients with subarachnoid hemorrhage. We examined a large multihospital data base to determine how practice is evolving with regard to the use of CT angiography and DSA in patients with ruptured cerebral aneurysm. MATERIALS AND METHODS: The Premier Perspective data base was used to identify hospitalizations of patients treated with clipping or coiling of ruptured cerebral aneurysms from 2006–2011. Billing information was used to determine pretreatment and posttreatment use of DSA and CT angiography during hospitalization. RESULTS: A total of 4972 patients (1022 clipping, 3950 coiling) at 116 hospitals were identified. The percentage of patients with SAH who underwent pretreatment CT angiography significantly increased from 20% in 2006 to 44% in 2011 (P < .0001), whereas the percentage of patients who underwent DSA remained unchanged from 96–94% (P = .28). This CT angiography trend was observed in coiling patients (17–42%, P < .0001) and clipping patients (32–54%, P < .0001). There was a significant increase in the percentage of patients who underwent posttreatment imaging from 41% in 2006 to 48% in 2011 (P = .0037). This trend was observed in clipping patients (33–65%, P < .0001) but not coiling patients (43–45%, P = .62). CONCLUSIONS: For the pretreatment evaluation of ruptured aneurysms, the use of CT angiography increased from 2006–2011 without a corresponding decrease in the use of DSA. These results raise the question of potential redundancy without added clinical value of the second test.